Sekolah Hijau: Inovasi Single Axis Solar Tracking System Dengan Sensor LDR Sebagai Alternatif Energi Listrik - Alda, Tania; Paulido Siahaan, Martin; Raja Guk Guk, Marco Bambang; Rajagukguk, Rosianna; Carolina Br Purba, Erida; Adelina Sitompul, Putri (LPPM ITEBA, 2025)
Indonesia as a tropical country has enormous potential to develop renewable energy with the help of technological advances to produce and develop more environmentally friendly energy. Because it is clean without waste gas and has few moving components, the use of solar cells or sunlight is very popular and is one way to convert solar energy into electrical energy. Schools that lack electrical power for teaching and learning activities can apply one of these methods of using solar energy. The partner of our service is the Dharma Pala Medan Private Elementary School, with a total of 38 students and a total of 6 teachers. The methods/stages of activities include partner surveys, program planning, outreach, designing and assembling a solar tracking system, equipment installation, partner education, and gradual program evaluation. The method used for data collection was interviews with teachers and students. The intensity of lighting in learning has a close relationship with eye fatigue so that it will interfere with learning concentration which will have an impact on students' interest in learning. Environmental factors such as lighting can have a positive and significant impact on a person's level of boredom